Fertility Preservation in Women with Cervical Cancer - Sellami, Ines; Saïs, Emine; Souare, Fatoumata; Becquart, Céleste; Thomas, Hélène; Sonigo, Charlotte; Grynberg, Michaël (Seminars in Reproductive Medicine, 2025)
Cervical cancer (CC) is one of the most common malignancies affecting young women of childbearing age, making fertility preservation (FP) a pivotal consideration in its management. The feasibility of FP techniques depends on the cancer stage and oncological treatments. In early-stage CC, fertility-sparing surgery can be offered for young patients wishing to preserve fertility without compromising oncological safety. Neoadjuvant chemotherapy followed by fertility-sparing surgery is an alternative for patients with nonmetastatic locally advanced disease and negative lymph node status. Nevertheless, for patients with locally advanced disease requiring radical hysterectomy or pelvic radiotherapy, FP can be performed using oocyte, embryo, or ovarian tissue cryopreservation. For these patients, future pregnancy is possible through surrogacy. Recently, uterine transposition has been proposed as an alternative to preserve uterine anatomy to prevent uterine radio-induced damage and avoid surrogacy. This review provides a comprehensive overview of the FP options available for young patients with CC.
Keywords: fertility preservation; fertility-sparing surgery; cervical cancer